Layered Si–Ti oxide thin films with tailored electrical and optical properties by catalytic tandem MLD-ALD. Issue 56 (29th October 2021) - Kalderon, Boaz; Sarkar, Debabrata; Killi, Krushnamurty; Danzig, Tamuz; Azulay, Doron; Millo, Oded; Cohen-Taguri, Gili; Yerushalmi, Roie
Abstract : Layer-by-layer deposition of Si–Ti layered oxide thin films are obtained using catalytic tandem M/ALD methodology. The films exhibit optical (RI) and electrical conductivities by selecting the MLD to ALD proportion in the super cycle. Abstract : Oxides with well-controlled optical and electrical properties are key for numerous advances in nanotechnology, including energy, catalysis, sensors, and device applications. In this study we introduce layer-by-layer deposition of silicon–titanium layered oxide (Si–Ti LO) thin films using combined MLD-ALD methodology (M/ALD). The Si–Ti LO film deposition is achieved by acid–base catalysis establishing an overall catalytic tandem M/ALD super cycle (CT-M/ALD). The catalytic nature of the process allows relatively fast deposition cycles under mild conditions compared with the typical cycle time and conditions required for ALD processes with silane precursors. The Si–Ti LO thin films exhibit tuneable refractive index and electrical conductivities. The refractive index is set by the stoichiometry of Si- to Ti-oxide phases simply by selecting the MLD to ALD proportion in the CT-M/ALD super cycle, with low and high refractive index, respectively. Thermal treatment of Si–Ti LO thin films resulted in conductive thin films with both graphitic and Magnéli oxide phases. Enhanced conductivity and reduced onset temperature for Magnéli phase formation were obtained owing to the unique Si–Ti layer structure and stoichiometry attained by the CT-M/ALD process and facilitated by breaking of Si–C bonds and Red–Ox reactions between the Si sub-oxide and TiO2 phases leading to the conductive Magnéli phase. Hence, the embedded amine silane functions not only for catalysing Si–Ti LO deposition but also to further promote subsequent transformations during thermal processing. This work demonstrates the concept of embedding a meta-stable organic motif by the MLD step to facilitate transformation of an oxide phase by taking advantage of precise layer-by-layer deposition of alternating phases enabled by M/ALD.